Part I. Respiratory system involvement in patients with rheumatoid arthritis - Ruzana Ramilovna Samigullina (Современная ревматология, 2013)
On 23–25 May 2013, the Karolinska Institute (Stockholm, Sweden) with the support of MSD company held a meeting on a Clinical Observational Program for rheumatologists, which was attended by the well-known rheumatologists and leading specialists of the Institute Prof. R. van Vollenhoven, Prof. L. Klareskog, Dr. E. af Klint, and Dr. C. Carlens. The reports and interactive sessions discussed the problems of rheumatoid arthritis (RA), including early RA (pathology, pathogenesis, and treatment), registers of with rheumatic diseases; ultrasound diagnosis of inflammatory locomotor diseases; biological therapy for rheumatic diseases; organization of work in the research immunological laboratory, outpatient/day hospital units of a rheumatology clinic. The Program was also attended by physicians from different European countries (Sweden, Germany, Russia, Spain, Greece, etc.). Below is given an overview of the proceedings of the Clinical Observational Program.